Conceptualising and measuring children's time use: a technical review for Young Lives - Vogler, P; Morrow, V; Woodhead, M (Young Lives, 2009)
This paper reviews interdisciplinary research on children's time use. Following the introduction, Section 2 sketches the broad historical and socio-cultural context for time-use studies, recognising that how childhood has been variously understood affects the valuation of children's activities, roles and relationships and the ways they are experienced. It will become clear that differing views about children's 'proper' time use have coincided with powerful assumptions about children's roles throughout history, and the 'value' of children's time. We offer a selective review of studies addressing time use from a range of disciplinary perspectives, in order to highlight how the use of time is not only associated with economic value, but also socio-cultural values. Whether or not certain children's activities are considered permissible, acceptable and appropriate by adult members of society largely depends upon how these activities fit into local value systems. Section 3 briefly explores subjective dimensions of time use, drawing on contrasting paradigms for studying how far children perceive time differently to adults. This question is addressed from a developmental psychological and social constructionist perspective. Finally, Section 4 offers an overview of research methods that have been utilised in studies of children's time use. This review is not exhaustive of methods in time-use research, but is intended as a summary resource for YL and other child researchers.